Re-starting or initiating guideline-recommended hypoglycemic agents for patients admitted with hyperglycemic crisis - Alshaya, Abdulrahman I.; Al-Yahya, Haya; Alshehri, Abdulmajeed; Alrashed, Mohammed; Alshaya, Omar; Alfehaid, Lama; Badreldin, Hisham A. (Frontiers in Medicine, 2025)
IntroductionHyperglycemic crises, such as diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS), are life-threatening complications of diabetes. This study aimed to assess the impact of early initiation of non-insulin hypoglycemic agents on glycemic variation following acute management of DKA/HHS.Research design and methodsThis retrospective cohort study was conducted at King Abdulaziz Medical City and King Abdullah Specialized Children Hospital in Riyadh, Saudi Arabia. Patients with diabetes mellitus admitted between January 2015 and December 2023 were included if they had a confirmed diagnosis of DKA or HHS and received any non-insulin hypoglycemic agents after receiving acute care management. The primary outcome was to assess the impact of early initiation (defined as less than 24–48 h) of non-insulin hypoglycemic agents following acute management of DKA/HHS in controlling glycemic variation by measuring delta blood glucose “BG,” with secondary outcomes including hypoglycemia incidence, correctional insulin requirements, predictors for hospital length of stay (LOS), 90-day mortality, and hospital readmissions. Data was adjudicated by a separate clinician. Statistical analysis was performed using SPSS (IBM, Armonk, NY).ResultsOut of 1,483 screened patients, 137 were included, experiencing a total of 226 hyperglycemic events. During hospitalization, 42.9% of patients were transitioned to oral hypoglycemic agents within 4 days. Transitioning to oral hypoglycemic medications resulted in a significant reduction in BG levels. Early re/initiation of hypoglycemic agents was strong predictor for shorter hospital LOS and lower 90-day mortality rate (2.1% vs. 10.1%, p-value = 0.02). There were no other significant outcomes.ConclusionThe study suggests that early initiation of non-insulin hypoglycemic results in similar delta BG compared to late initiation following acute management of DKA and HHS. The findings indicate that early transitioning to non-insulin hypoglycemic agents is associated with a lower 90-day mortality rate after acute management of DKA/HHS and a strong predictor for shorter hospital LOS. Further research, including randomized controlled trials, is recommended to validate these findings and explore long-term effects on mortality and clinical outcomes.